2015
DOI: 10.1007/s11356-015-4606-4
|View full text |Cite
|
Sign up to set email alerts
|

Ecological, morphological, and histological studies on Blaps polycresta (Coleoptera: Tenebrionidae) as biomonitors of cadmium soil pollution

Abstract: Soil pollution in Egypt became far more serious than before due to either the heavy usage of different toxic pesticides or aerosol deposition of industrial pollutants. The present mentioned ground beetle, Blaps polycresta Tschinkel 1975 (Coleoptera: Tenebrionidae), showed ecological, morphological, and histological alterations in adult insects as biomonitors. Two cultivated sites (reference and polluted) were chosen for sampling the insects. The results indicated a significant increase in soil cadmium concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 29 publications
5
23
1
Order By: Relevance
“…In contrast to our study, Jiang et al found that female/male pupal weights of Lymantria dispar (Coleoptera: Lymantriidae) were significantly decreased under Cd stress [43]. Similar reduction effects of Cd on body weight were reported in Blaps polycresta (Coleoptera: Tenebrionidae) [44]. The body weight of another insect species, Spodoptera exigua (Lepidoptera: Noctuidae), was not effected by Cd exposure [41].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In contrast to our study, Jiang et al found that female/male pupal weights of Lymantria dispar (Coleoptera: Lymantriidae) were significantly decreased under Cd stress [43]. Similar reduction effects of Cd on body weight were reported in Blaps polycresta (Coleoptera: Tenebrionidae) [44]. The body weight of another insect species, Spodoptera exigua (Lepidoptera: Noctuidae), was not effected by Cd exposure [41].…”
Section: Discussioncontrasting
confidence: 54%
“…Sun et al reported that a high concentration of Ni damaged the quality of sperm bundles, resulting in a decrease of the oviposition and hatching rates in Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae) [46]. Additionally, Osman et al showed that Cd exposure caused general necrosis and shape change with distorted chromatin materials in oocytes, which damaged female gonads of the ground beetle, Blaps polycresta (Coleoptera: Tenebrionidae) [44].…”
Section: Discussionmentioning
confidence: 99%
“…The size of the body of some species of ground beetles decreases in urban habitats (Weller & Ganzhorn, 2004;Sukhodolskaya, 2013). Researchers have also identified the effects of heavy metal pollution: zinc, lead, cadmium on the morphometric features of ground beetles (Lagisz, 2008;Osman et al, 2015;Sowa & Skalski, 2019). Females from polluted zones are smaller than females from the control populations.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, finding of the accumulation of metals concentration is more accurate and higher in the whole body than a single organ in insects (Cain et al, 1995). Among the famous and distributed insects in any habitat in addition to widely monitoring the accumulation of heavy metals were ants (Belskii and Belskaya, 2013;Skaldina et al, 2018), beetles (Bednarska et al, 2013;Osman et al, 2015;Zhou et al, 2019), and grasshopper ( Del Toro et al, 2010;Mustafa and El-Shazly, 2017) they consider as good bioindicator for metal pollution especially in industrial areas.…”
Section: Introductionmentioning
confidence: 99%